Inflammation, Thrombosis, and Destruction: The Three-Headed Cerberus of Trauma- and SARS-CoV-2-Induced ARDS - Lupu, Ludmila; Palmer, Annette; Huber-Lang, Markus (Frontiers in Immunology, 2020)
Physical trauma can be considered an unrecognized “pandemic” because it can occur anywhere, affect anyone and represents a global burden. Following severe tissue trauma, patients frequently develop acute lung injury (ALI) and/or acute respiratory distress syndrome (ARDS) despite modern surgical and intensive care concepts. The underlying complex pathophysiology of life-threatening ALI/ARDS has been intensively studied in experimental and clinical settings. However, currently, the coronavirus family has become the focus of ALI/ARDS research because it represents an emerging global public health threat. The clinical presentation of the infection is highly heterogeneous, varying from a lack of symptoms to multiple organ dysfunction and mortality. In a particular subset of patients, the primary infection progresses rapidly to ALI and ARDS. The pathophysiological mechanisms triggering and driving SARS-CoV-2-induced ALI/ARDS are still poorly understood. Although it is also generally unknown whether insights from trauma-induced ARDS may be readily translated to SARS-CoV-2-associated ARDS, it was still recommended to treat coronavirus-positive patients with ALI/ARDS with standard protocols for ALI/ARDS. However, this strategy was questioned by clinical scientists, because it was documented that some severely hypoxic SARS-CoV-2 infected patients exhibited a normal respiratory system compliance, a phenomenon rarely observed in ARDS patients with another underlying etiology. Therefore, coronavirus-induced ARDS was defined as a specific ARDS phenotype, which accordingly requires an adjusted therapeutic approach. These suggestions reflect previous attempts of classifying ARDS into different phenotypes that might overall facilitate ARDS diagnosis and treatment. Based on the clinical data from ARDS patients, two major phenotypes have been proposed: hyper- and hypo-inflammatory. Here, we provide a comparative review of the pathophysiological pathway of trauma-/hemorrhagic shock-induced ARDS and coronavirus-induced ARDS, with an emphasis on the crucial key points in the pathogenesis of both these ARDS forms. Thereby, the manifold available data on trauma-/hemorrhagic shock-induced ARDS may help to better understand coronavirus-induced ARDS.